Effect Size: A guide for researchers and users - Coe, Robert (2003)
The present article describes a method to quantify the magnitude of the differences between two measures and/or the degree of the effect of a variable about criteria, and it is named likethe effect size measure, d. Use it use in research and applied contexts provides a quitedescriptive complementary information, improving the interpretation of the results obtained bythe traditional methods that emphasize the statistical significance. Severa) forms there are of interpreting the d, and an example taken of an experimental research, is presented to clarify the concepts and necessary calculations. This method is not robust to sorne conditions that they candistort its interpretation, for example, the non normality of the data; alternative methods are mentioned to the statistical d. We ending with sorne conclusions that will notice about the appropriate use of it.